Assessing the risk for development of Venous Thromboembolism (VTE) in surgical patients using Adapted Caprini scoring system. (June 2016) - Bilgi, Kanchan; Muthusamy, Anitha; Subair, Mohsina; Srinivasan, Sanjeev; Kumar, Arun; Ravi, Ramya; Kumar, Ranjith; Sureshkumar, Sathasivam; Mahalakshmy, T.; Kundra, Pankaj; Kate, Vikram
Abstract: Aim: To determine the incidence, morbidity and mortality due to Venous Thromboembolism (VTE) in surgical patients, and to assess the validity and reliability of Adapted Caprini scoring in risk stratification for VTE prophylaxis. Methodology: This was a prospective observational study in a tertiary care hospital of South India on patients who underwent both elective and emergency surgeries over a period of 9 months. An Adapted Caprini score was devised which included only the clinical criteria. The patients were scored by two persons independently at admission and followed up till the 30th post-operative day and primary and secondary end points were statistically analyzed. Results: Three hundred and one patients were included and the overall incidence of VTE at 30 days was 7.3%. The risk of developing VTE was found to be significantly higher among the >8 score group as compared to 3–4 group (OR = 153.5, p < 0.001), or the 5–6 group (OR = 52.9, p < 0.001) or the 7–8 group (OR = 2.3, p = 0.002). Patients with a score of 7–8 were more likely to develop VTE as compared to 3–4 group (OR = 67.5, p < 0.001) or the 5–6 group (OR = 23.2, p < 0.001). Conclusion: The risk of developing VTE is less significant in the 5–6 score group compared to 7–8 or more score group. Further stratification of the highest risk groups is recommended to provide appropriate prophylaxis only to the patients with high scores, thereby reducing complications due to VTE prophylaxis. Highlights: Prospective observational study to assess validity of Adapted Caprini scoring in the risk stratification for VTE prophylaxis. Risk of VTE significantly higher in >8 score group compared to 3–4 (p < 0.001), 5–6 (p < 0.001) or the 7–8 group (p = 0.002). Patients with score 7–8 more likely to develop VTE compared to 3–4 (OR = 67.5, p < 0.001) or 5–6 groups (OR = 23.2, p < 0.001). Unlike Western population, present study found within high-risk group (score >5), risk of VTE is not significant in 5–6 group. Adapted Caprini RAM is economical, practical & effective tool to stratify general surgical patients for perioperative VTE risk.